Technology Transformation in Education: Mathematics Learning Media in the Digitalization Era - Agnesa, Tia; Desmayanasari, Dwi; Nuraida, Elis Muslimah; Sahanata, Meirisa; Ghoer, Fadila Rahma (Universitas Negeri Padang, 2023)
The use of technology plays a very crucial role in the process of learning mathematics. The main factor for the success of integrating technology into learning mathematics is the will and determination to adapt to transformation through designing learning designs through the right learning tools and resources, including various types of media. This study intends to assess the effectiveness of the application of media in learning mathematics at the Faculty of Tarbiyah and Teacher Training at UIN Sulthan Thaha Saifuddin Jambi. Descriptive methods are used to analyze lecturers' abilities in managing learning, student activities, student responses, and student learning outcomes. Based on the descriptive analysis of the research findings, it can be concluded that the integration of instructional media in Mathematics Learning at the Faculty of Tarbiyah and Teacher Training at UIN Sulthan Thaha Saifuddin Jambi has proven effective. This can be seen in the effectiveness of the lecturer's ability to manage learning, the active participation of students, the positive response of students to learning, and the overall achievement of learning outcomes. In this way it can be concluded that the implementation of media in Mathematics Learning at the Faculty of Tarbiyah and Teacher Training at UIN Sulthan Thaha Saifuddin Jambi has proven successful and produced effective results.